2021
DOI: 10.1101/2021.11.05.21265958
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Length of hospital stay and risk of intensive care admission and in-hospital death among COVID-19 patients in Norway: a register-based cohort study comparing patients fully vaccinated with an mRNA vaccine to unvaccinated patients

Abstract: ObjectivesWith most of the Norwegian population vaccinated against COVID-19, an increasing number and proportion of COVID-19 related hospitalisations are occurring among vaccinated patients. To support patient management and capacity planning in hospitals, we estimated the length of stay (LoS) in hospital and odds of intensive care (ICU) admission and in-hospital mortality among COVID-19 patients ≥18 years who had been vaccinated with an mRNA vaccine, compared to unvaccinated patients.MethodsUsing national reg… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
3

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
2
6
0
3
Order By: Relevance
“…In a register-based cohort study of 3,203 patients in Norway by Whittaker et al [20], fully vaccinated patients had a lower risk of ICU admission which is similar to our study; however, they observed no differences in mortality among vaccinated and unvaccinated patients. Although there were no significant differences in LOS among vaccinated and unvaccinated in our study, shorter LOS among vaccinated patients was reported in their study.…”
Section: Plos Onesupporting
confidence: 90%
“…In a register-based cohort study of 3,203 patients in Norway by Whittaker et al [20], fully vaccinated patients had a lower risk of ICU admission which is similar to our study; however, they observed no differences in mortality among vaccinated and unvaccinated patients. Although there were no significant differences in LOS among vaccinated and unvaccinated in our study, shorter LOS among vaccinated patients was reported in their study.…”
Section: Plos Onesupporting
confidence: 90%
“…In this study, we used the daily numbers of new cases and new deaths in analyzing the situation of each country's situation of COVID‐19 14 . In addition, we had the daily new death lagged for 7 days since there was suggested an interim between SARS‐CoV‐2 infection and the related death, which was estimated and averaged as 8 days 15,16 . The average incidence was calculated by the average daily new cases and population size.…”
Section: Methodsmentioning
confidence: 99%
“…SARS-CoV-2 infection is defined as a positive SARS-CoV-2 PCR test reported to the MSIS registry, which has been complete for all domestic laboratories since April 2020. Individuals who were hospitalised or admitted to an intensive care unit (ICU) with COVID-19 are registered in NIPaR, which covers mandatory reporting from all Norwegian hospitals [25]. We included all hospitalisation where COVID-19 was registered as the primary diagnosis for admission and ICU admission of individuals who tested positive for SARS-CoV-2 and were admitted to an ICU (length of stay ≥ 24 h), required mechanical ventilatory support (invasive or non-invasive), or persistent administration of vasoactive medication.…”
Section: Definitionsmentioning
confidence: 99%